2023
DOI: 10.3390/ijms242015375
|View full text |Cite
|
Sign up to set email alerts
|

1,5,6-Trimethoxy-2,7-dihydroxyphenanthrene from Dendrobium officinale Exhibited Antitumor Activities for HeLa Cells

Chong Liang,
Chonglun Zhang,
Yinlin Zhuo
et al.

Abstract: Natural products are irreplaceable reservoirs for cancer treatments. In this study, 12 phenanthrene compounds were extracted and isolated from Dendrobium officinale. Each chemical structure was identified using comprehensive NMR analysis. All compounds were evaluated for their cytotoxic activities against five tumor cell lines, i.e., HeLa, MCF-7, SK-N-AS, Capan-2 and Hep G2. Compound 5, 1,5,6-trimethoxy-2,7-dihydroxyphenanthrene, displayed the most significant cytotoxic effect against HeLa and Hep G2 cells, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The previous studies reported terpenoids, 3 bibenzyl derivatives, 1–7 polysaccharides, 8–15 are the main components of this plants. Some of which exhibited antitumor, 7,14,15 anti-inflammatory activities 8–13 and alleviates type 2 diabetes mellitus. 9 Therefore, the whole plants of D. officinale were selected for further study.…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies reported terpenoids, 3 bibenzyl derivatives, 1–7 polysaccharides, 8–15 are the main components of this plants. Some of which exhibited antitumor, 7,14,15 anti-inflammatory activities 8–13 and alleviates type 2 diabetes mellitus. 9 Therefore, the whole plants of D. officinale were selected for further study.…”
Section: Introductionmentioning
confidence: 99%